Characterization of the killer toxin KTCf20 from wickerhamomyces anomalus, a potential biocontrol agent against wine spoilage yeasts - Fernandez de Ullivarri, Miguel (2018)
Wickerhamomyces anomalus Cf20 secretes the killer toxin KTCf20 that inhibits several wine spoilage yeasts of the species Pichia guilliermondii, P. membranifaciens, Brettanomyces bruxellensis and Dekkera anomala. KTCf20 binds cell wall extracts from the sensitive target P. guilliermondii Cd6; however, this capacity was lost when cell wall extracts were pre-treated with fungal β-glucanase. Pustulan and laminarin inhibited killer activity, suggesting that β-1,3 and β-1,6-glucans may be the putative binding sites for KTCf20 on the cell wall of sensitive cells. The toxin was produced and showed to be stable and highly active at physicochemical conditions suitable for winemaking process. In addition, the strain Cf20 is compatible with Saccharomyces cerevisiae in co-culture conditions being potential its application in a mixed starter culture. These data suggest that W. anomalus Cf20 and/or KTCf20 are promising biocontrol agents against spoilage yeasts during wine-making process.